TO FIND OUT THE EFFECT OF VARIOUS BODY POSITIONS ON PEAK EXPIRATORY FLOW RATE (PEFR) IN COPD PATIENTS (International Journal of Physiotherapy, 2016)
Background: COPD is the second most common lung disorder. Respiratory mechanics of COPD is altered. Lung volumes & biomechanical changes lead to weak & ineffective expiratory maneuvers.Methods: 40 COPD subjects above the age of 45years were selected through purposive sampling. The subjects were placed in seven different positions namely Standing, Chair sitting, Long sitting, Semi fowler’s position, Supine, Side lying, Head down. Following this the subject performed three tests of PEFR with intermittent rest period as preferred by the subject between each trial.Results: PEFR achieved by subjects with COPD were significantly affected by body position. Standing (161.82) led to results which were significantly higher than all other positions followed by chair sitting (150.079), long sitting (141.495),semi fowler’s position (136.746), supine lying (126.829), side lying (120.162) and head low position (107.829) led to results which were significantly lower than all other positions.Conclusion: More the upright position, higher the PEFR. PEFR is more in standing and Head down position has the lowest PEFR value. Increased lung volumes in standing position can be related to the increased thoracic cavity volume owing to the effect of gravity and the inspiratory muscles would be able to expand the unrestricted thorax in all directions in this position & expiratory muscles attain their optimal length during standing.